Perbedaan kecerdasan emosional dan hasil belajar Kalkulus Mahasiswa Jurusan Kimia ditinjau dari jalur masuk - Sutamrin Sutamrin; Sahid Sahid (Seminar Nasional LP2M UNM, 2019)
This research is a study that aims to determine the differences in emotional intelligence and student learning outcomes which are viewed from the student entrance path, namely the SNMPTN, SBMPTN and Mandiri pathways. To reach the target of the study, 2 instruments were used, namely 1) an instrument to measure emotional intelligence in the form of a questionnaire, 2) an instrument for measuring student calculus learning outcomes. The population in this study were students majoring in Chemistry FMIPA UNM Makassar 2018/2019 academic year. While the samples in the study were students majoring in chemistry who programed the calculus courses of class A and B of Chemical Education Study Program. The data analysis technique used is inferential statistical analysis using ANOVA test. The results of this study obtained F-count = 1.94 <FTabel = 3.129 for the learning outcomes test and F-count = 0.26 <FTabel = 3.129 for emotional intelligence. This means that the variables of emotional intelligence and student calculus learning outcomes are not significantly different from students who enter through the SNMPTN, SBMPTN and Mandiri pathways.